Virtual reality-based treatment for regaining upper extremity function induces cortex grey matter changes in persons with acquired brain injury - Keller, Jiří; Štětkářová, Ivana; Macri, Vince; Kühn, Simone; Pětioký, Jakub; Gualeni, Stefano; Simmons, С Douglas; Arthanat, Sajay; Zilber, Paul (Journal of neuroengineering and rehabilitation, 2020)
BACKGROUND: Individuals with acquired brain injuries (ABI) are in need of neurorehabilitation and neurorepair. Virtual anatomical interactivity (VAI) presents a digital game-like format in which ABI survivors with upper limb paresis use an unaffected limb to control a standard input device and a commonplace computer mouse to control virtual limb movements and tasks in a virtual world. METHODS: In a prospective cohort study, 35 ambulatory survivors of ABI (25/71% stroke, 10/29% traumatic brain injury) were enrolled. The subjects were divided into three groups: group A received VAI therapy only, group B received VAI and physical/occupational therapy (P/OT), and group C received P/OT only. Motor skills were evaluated by muscle strength (hand key pinch strength, grasp, and three-jaw chuck pinch) and active range of motion (AROM) of the shoulder, elbow, and wrist. Changes were analyzed by ANOVA, ANCOVA, and one-tailed Pearson correlation analysis. MRI data was acquired for group A, and volumetric changes in grey matter were analyzed using voxel-based morphometry (VBM) and correlated with quantified motor skills. RESULTS: AROM of the shoulder, elbow, and wrist improved in all three groups. VBM revealed grey matter increases in five brain areas: the tail of the hippocampus, the left caudate, the rostral cingulate zone, the depth of the central sulcus, and the visual cortex. A positive correlation between the grey matter volumes in three cortical regions (motor and premotor and supplementary motor areas) and motor test results (power and AROM) was detected. CONCLUSIONS: Our findings suggest that the VAI rehabilitation program significantly improved motor function and skills in the affected upper extremities of subjects with acquired brain injuries. Significant increases in grey matter volume in the motor and premotor regions of affected hemisphere and correlations of motor skills and volume in nonaffected brain regions were present, suggesting marked changes in structural brain plasticity. TRIAL REGISTRATION: The trial "Limitations of motor brain activity - use of virtual reality for simulation of therapeutic interventions" has been registered under reference number ISRCTN11757651 .
Keywords: Brain Injuries; senioři; Brain plasticity; Stroke; videohry; obnova funkce; Middle Aged; mužské pohlaví; rehabilitace po cévní mozkové příhodě; mozek; Prospective Studies; Adult; Virtual Reality; Virtual world; magnetická rezonanční tomografie; Magnetic Resonance Imaging; Brain; Video Games; ženské pohlaví; Stroke Rehabilitation; Recovery of Function; Humans; prospektivní studie; Rehabilitation; poranění mozku; Traumatic brain injury (TBI); Virtual anatomical interactivity (VAI); lidé středního věku; Occupational Therapy; Therapeutic games; Magnetic resonance imaging (MRI); virtuální realita; dospělí; Acquired brain injury (ABI); Female; Aged; Video-observation-feedback therapy; lidé; Male; ergoterapie